2014
DOI: 10.1111/clr.12447
|View full text |Cite
|
Sign up to set email alerts
|

Fresh extraction socket: spontaneous healing vs. immediate implant placement

Abstract: Immediate implant placement into fresh extraction sockets may jeopardize the vertical bone remodelling of the socket. Furthermore, a tendency towards greater buccal horizontal resorption was observed in the most coronal aspect of the buccal bone crest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
2
21
2
Order By: Relevance
“…The resulting position of the buccal bone crest, 2.2 mm apical of its lingual counterpart in the control group, was larger than what has been reported for the spontaneous healing of alveolar sockets (VBLs of 1-2 mm) (Discepoli et al, 2015;Vignoletti et al, 2009).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The resulting position of the buccal bone crest, 2.2 mm apical of its lingual counterpart in the control group, was larger than what has been reported for the spontaneous healing of alveolar sockets (VBLs of 1-2 mm) (Discepoli et al, 2015;Vignoletti et al, 2009).…”
Section: Discussioncontrasting
confidence: 62%
“…The resulting position of the buccal bone crest, 2.2 mm apical of its lingual counterpart in the control group, was larger than what has been reported for the spontaneous healing of alveolar sockets (VBLs of 1–2 mm) (Discepoli et al, ; Vignoletti et al, ). This discrepancy can be explained by differences in the anatomy of the residual bone walls among the different animals used in these experimental studies.…”
Section: Discussionmentioning
confidence: 57%
“…At eight weeks of healing, the buccal bone wall reduction at control sites was 0.18 ± 0.08mm while at implant sites it was reported to be 0.94 ± 0.12mm, in other words, two or three times greater. The vertical distance between the buccal and the lingual bone increased during the healing period at the immediate implant sites while it kept unchanged at the natural healing sites (Discepoli et al 2014). Both investigations concluded that, immediate implant placement not only does not avoid dimensional changes of the alveolar ridge but even results in a greater resorption, possible caused by the additional surgical trauma.…”
Section: Hard and Soft Tissue Changes After Immediate Implant Placementmentioning
confidence: 93%
“…However, evidence from animal and human studies have shown that implant installation does not interfere with bone remodeling (Boticelli et al 2004(Boticelli et al , 2006Araujo et al 2005Araujo et al , 2006Sanz et al 2009;Ferrus et al 2010;Tomasi et al 2010;Discepoli et al 2014). …”
Section: Hard and Soft Tissue Changes After Immediate Implant Placementmentioning
confidence: 99%
See 1 more Smart Citation